Pemanfaatan Teknologi Cubeacon Sebagai Media Informasi Di UK Petra - Yosua Umbu Datu Kadiwanu; Alexander Setiawan; Rudy Adipranata (Jurnal Infra, 2020)
Along with the development of technology today, the communication media is switching from conventional media to new media. Although in the transition to new media, users still miss some of the information that has been given in the form of a handbook containing important information, and still questioning to others to obtain information. To overcome this, Cubeacon technology is used to help maximize the dissemination of information by sending information to the user when the user approaches or is around the beacon coverage by utilizing the Bluetooth signal emitted by the beaconCubeacon is a device that communicates with smartphone using Bluetooth signals. With Bluetooth Low Energy based wireless technology that sends bluetooth signals continuously containing minor and major values from Cubeacon, the smartphone will provide information based on what stored in the database.The test results indicate that the beacon placement can affect the quality of the emitted signal. This application can be used by users to find information from beacons within the reach of a smartphone.